Diet intervention to improve cardiovascular risk factors among Iranian postmenopausal women - Abedi, Parvin; Huang, Mary Soo Lee; Kandiah, Mirnalini; Yassin, Zaitun; Shojaeizadeh, Davoud; Hosseini, Mostafa; Malihi, Reza (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2010)
Cardiovascular disease is a leading cause of death and disability and remains so in the future. The aim of this study was to detect the impact of a 6-month diet intervention on cardiovascular risk factors in postmenopausal Iranian women. It was a randomized controlled trial that carried out in the East Health Clinic in Ahvaz- Iran. This study started on June 2007 and was completed on May 2008. A total 64 healthy postmenopausal women recruited and randomly assigned to the intervention group (35) and control (29). Over the six months follow-up, the intervention group received five educational sessions (two face to face and three lecture discussion classes with slide demonstration) at the first month. These sessions were about menopause, cardiovascular disease and healthy diet. Every participant in the intervention group received one face to face education session at the 3rd month, and also received a telephone call at the end of each month starting with the second month to remain on the diet. Pre-intervention and post-intervention anthropometric measurements, blood pressure, blood lipids and dietary intake were assessed. Data analyzed using the SPSS version 15. Descriptive (means and SD), univariate (Paired-t test, Chi-Square and Independent T-test) and multivariate (GLM Repeated Measure) statistics were used. Participants in the diet group had significantly lower weight (-0.9 kg), body mass index (-0.4 kg/m2), and fasting blood sugar (-4.5 mg/dl). The diet group significantly increased their daily intake of fiber (+2.3 g, P = 0.05), decreased their intake of sodium (-28 mg, P = 0.04), and consumption of fruit and vegetable ≥ 5 serving a day (80%, P = 0.03) compared to the control group. Post menopausal women are at a greater risk for cardiovascular disease. Healthy diet using educational intervention can be an effective means of reducing cardiovascular risk in postmenopausal women.